Bone marrow B lymphocytes in multiple myeloma and MGUS: Focus on distribution of naïve cells and memory subsets. (October 2016) - Pojero, Fanny; Casuccio, Alessandra; Giambanco, Caterina; Bulati, Matteo; Buffa, Silvio; Di Bassiano, Francesco; Gervasi, Francesco; Caruso, Calogero; Colonna Romano, Giuseppina
Highlights: Bone marrow B cell subsets are differentially distributed in myeloma patients. Fraction of DN B cells is increased in patients unable to reach complete response. Naïve/transitional B cells are expanded in stringent complete responders. DN and naïve/transitional B cells may be monitored with predictive purposes. Abstract: Background/Aims: Multiple myeloma (MM) is caused by proliferation of clonal plasma cells (cPCs) in bone marrow (BM), associated with numerical and functional defects in immune subsets. An impairment of B cell compartment is involved in onset/progression of the disease. Methods: By flow cytometry, we studied distribution of naïve/transitional (IgD + CD27 − ), memory unswitched (IgD + CD27 + ), memory switched (IgD − CD27 + ) and double negative (DN) (IgD − CD27 − ) B lymphocytes in BM of control subjects, and responding and relapsing patients. Results: We observed an increased percentage of IgD + CD27 + B cells in healthy controls vs responding patients (p < 0.05). Treated non complete responders exhibited an expanded DN compartment vs stringent complete responders (p = 0.011); in turn IgD + CD27 − subpopulation was larger in stringent complete responders vs other responding patients (p = 0.006). None of the studied B cell subsets showed clonal restriction. Correlation analysis revealed negative correlations between naïve/transitional and DN B cells in all groups, except in newly diagnosed subjects. Conclusions: This may be considered a feasible start point to explore the importance of B cells in the immunosuppressive MM BM microenvironment, correlating these findings with immunosenescence and therapy related increased risk of infection. Moreover, we propose a possible role of naïve/transitional and DN B cells as predictive markers in treated patients.